The Obama presidency and the politics of change - Ashbee, Edward ; Dumbrell , John (Palgrave Macmillan, 2020)
Contents: Introduction : The politics of change Edward and John Dumbrell -- Obama's electoral record : the emerging Democratic majority? Philip J. Davies -- The Obama White House and Congress J David Morgan -- The US Supreme Court in the Obama years Helen J. Knowles, Steven B. Lichtman, and Brandon T. Metroka -- Continuity and change : immigration worksite enforcement in the Bush and Obama administrations Camille Marienbach and Andrew Wroe -- Macroeconomic policy and processes of neoliberalization during the Obama years Edward Ashbee -- Racially polarised partisanship and the Obama presidency Richard Johnson -- Offers and throffers : education policy under Obama Ursula Hackett -- Healthy hunger-free kids? The US school lunch revolution Clodagh Harrington -- Obama and the environment John C. Berg -- A new "war on poverty"? A story of policy success, frustration and restraint Alex Waddan -- Barack Obama and the return of 'declinism' : rebalancing American foreign policy in an era of multipolarity Andrew Moran -- Obama and Iran : explaining policy change Steven Hurst -- "Here, we see the future" : the Obama administration's pivot to Asia Niels Bjerre-Poulsen -- Afterword : the American Politics Group (Political Studies Association, UK) Dean McSweeney.